Governance mechanisms and Islamic bank performance: insights from South East Asia and the Gulf Cooperation Council / Fahru Azwa Mohd Zain, Wan Amalina Wan Abdullah and Siti Fariha Muhamad - Mohd Zain, Fahru Azwa; Wan Abdullah, Wan Amalina; Muhamad, Siti Fariha (Accounting Research Institute (ARI), Universiti Teknologi MARA, Shah Alam, 2025)
This study explores how corporate governance (CG) disclosure influences the relationship between governance mechanisms and the financial performance of Islamic banks in Southeast Asia (SEA) and the Gulf Cooperation Council (GCC) regions. Using panel data analysis and structural equation modelling (SEM), data from 33 Islamic banks in SEA and 46 in the GCC, covering the period from 2012 to 2021, was analysed to capture both pre- and postCOVID-19 effects. The study examines various governance mechanisms, including corporate governance practices, Shari’ah supervisory boards (SSBs), and legal systems. The findings show that strong governance mechanisms positively affect bank performance, with CG disclosure playing a key role in this relationship. Specifically, CG disclosure has an independent positive impact on bank performance. The research highlights that effective governance structures, such as SSBs and strong legal frameworks, lead to better performance. It also stresses the importance of precise CG disclosure requirements to improve financial stability and trust in Islamic banks. This study offers valuable insights into how Islamic governance mechanisms, especially those aligned with Shari’ah principles, influence the performance of banks, and provides a basis for future research in this field.